Emma Liggins. The Haunted House in Women’s Ghost Stories: Gender, Space and Modernity, 1850-1945 - Osoliová, Viktória (FOCUS: Papers in English Literary and Cultural Studies, 2022)
People have always been interested in the supernatural, which reveals our fascination with ghosts, spectral appearances and haunting. The popularity of the ghost story in the Victorian period has been thoroughly explored in relation to spiritualism, superstition, funerary practices, despite skepticism about the supernatural. Ghost literature became increasingly popular, especially among female authors. The Haunted House in Women’s Ghost Stories: Gender, Space and Modernity, 1850–1945 by Emma Liggins focuses on Victorian and modernist haunted house narratives in ghost stories by female authors such as Elizabeth Gaskell, Margaret Oliphant, Vernon Lee, Edith Wharton, May Sinclair, and Elizabeth Bowen.